Controlling impurity transport in 5D gyrokinetic simulations using a transport barrier - G. Lo-Cascio; E. Gravier; M. Lesur; T. Réveillé; Y. Sarazin; X. Garbet; K. Lim; T. Rouyer; A. Guillevic (Nuclear Fusion)
The effects of transport barriers on impurity transport, specifically helium (He) and tungsten (W), are investigated using the global, flux-driven, full-F, 5D gyrokinetic code GYSELA. The transport barrier is induced by triggering E  ×  B shear via an external poloidal momentum source, thereby stabilizing ITG turbulence and reducing outward heat fluxes. These reductions in particle and heat fluxes due to the transport barrier lead to enhanced confinement, thereby steepening the ion temperature profiles and reducing the heat diffusivity of the main ion species (i.e. deuterium). Impurity transport in both turbulent and neoclassical regimes is investigated under various conditions, with and without the transport barrier, along with a reversed density profile for tungsten. The transport barrier is found to reduce outward impurity transport and enhance neoclassical thermal screening due to the steepened temperature profile. However, it also prevents helium from being flushed out, due to an increased inward Banana-Plateau flux, caused by the poloidal asymmetry of the source. Overall, a transport barrier induced by an E  ×  B shear proves to be an effective mechanism not only for reducing heat fluxes but also for controlling impurity transport.